Personagens em construção no Memorial de Maria Moura : estudo da gênese do Beato Romano - Pacheco, Antonio Carlos de Miranda (2007)
The study of the literary manuscript allows us to observe the aspects of the artistic production that this piece is not able to present to the public. Following the Genetic Criticism s presupposes, associated to other knowledge fields, the critic may go along ways which were never tread. Thus, in this thesis, we looked for the creative forerunner of Rachel de Queiroz in/to the elaboration of the piece Memorial de Maria Moura, especially in what is concerned to the composition of the character Beato Romano , the priest José Maria. After delimitating the field for the Genetic Criticism s performance, differing this subject from the Textual Criticism, it was selected the corpus, among more than 2000 folios that compose the document of process of the mentioned novel , as it was classified the piece. The analysis of the author s Agenda and other documents of process, named here as Single Documents allow us to investigate the elaboration as well as the continuous valorization of a character who assumes the capital significance in this piece.